Study on the fuzzy proportional–integral–derivative direct torque control strategy without flux linkage observation for brushless direct current motors. (13th June 2019) - Peicheng, Shi; Suo, Wang; Rongyun, Zhang; Ping, Xiao
Considering the difficulty in setting and observing the flux linkage in the existing direct torque control for the brushless direct current motor, which is the cumbersome torque calculation method in direct torque control systems without flux linkage observation, the torque observation, voltage vector selection, and speed loop were studied further in such systems. The fuzzy proportional–integral–derivative direct torque control strategy is presented without flux linkage observation. In terms of torque observation, the cumbersome counter electromotive force calculation method was abandoned, and observation was made combining the three-phase current and Hall signal. In terms of optimal choice of voltage vector, the voltage vector selection table was built using the voltage hysteresis output and Hall signal. In terms of rotation speed control, the adaptive fuzzy proportional–integral–derivative was used to replace the traditional proportional–integral–derivative for the proportional–integral–derivative parameter self-adjustment. A control system simulation model was set up in MATLAB/Simulink for simulation verification. A hardware experimental platform was set up using DSP2812 as the main control board for experimental verification. The research results show that the fuzzy proportional–integral–derivative direct torque control without flux linkage observation further increased the dynamic response rate of the motor speed and reduced the electromagnetic torque ripple amplitude; thus, it is more suitable for application in high-precision and high-stability systems.